Students’ Mathematical Anxiety during the Covid-19 Pandemic and Its Impact on Deaf Students’ Mathematics Learning Outcomes - Mahayukti, Gst Ayu; Dewi, Putu Kartika; Suarsana, I Made; Hartawan, I Gusti Nyoman Yudi (Unnes Journal of Mathematics Education, 2024)
The emergence of various problems during online learning must receive attention, especially for special needs students. For deaf children, online learning problems in mathematics lessons will become more complex due to communication barriers (hearing loss). This study aims to analyze deaf children's mathematical anxiety in learning mathematics and its correlation to the deaf children’s learning outcomes during the Covid-19 pandemic. This research was descriptive and correlational research types. The subject research was deaf children at the SMP Luar Biasa Negeri Tuna Rungu. The study sample was 24 students. Research data was collected by observation, interviews, questionnaires, and tests. The data analysis used was descriptive analysis and simple regression. The results showed that deaf children's mathematical anxiety was very high. The results of the regression analysis show that mathematical anxiety has a significant effect on mathematics learning outcomes. Even though online learning during the pandemic has made the implementation of mathematics learning flexible because it can accommodate different learning styles of children, many obstacles were found in the learning process, given the limitations of deaf children, and they preferred offline learning. The implications of this research are expected to be an evaluation for teachers and deaf children to improve mathematics learning outcomes and to overcome deaf children's mathematical anxiety.